Proposal and design methodology of switching mode low dropout regulator for Bio-medical applications - Kenya Kondo; Hiroki Tamura; Koichi Tanno (Institute of Advanced Engineering and Science, 2019)
The switching operation based low dropout (LDO) regulator utilizing on-off control is pre-sented. It consists of simple circuit elements which are comparator, some logic gates, switched capacitor and feedback circuit. In this study, we target the application to the power supply circuit for the analog front end (AFE) of bio-medical system (such as daily-used bio-monitoring devices) whose required maximum load current is 50 A. In this paper, the design procedure of the proposed LDO has been clarified and actual circuit design using the procedure has been done. The proposed LDO has been evaluated by SPICE simulation using 1P 2M 0.6 m CMOS process device parameters. From simulation results, we could confirm that the low quiescent current of 1 A with the output ripple of 5 mVpp. The circuit area is 0.0173 mm2 in spite of using 0.6 m design rules. The proposed circuit is suitable for adopting to the light load and low frequency applications.